2015
DOI: 10.1002/2014jf003233
|View full text |Cite
|
Sign up to set email alerts
|

Where river and tide meet: The morphodynamic equilibrium of alluvial estuaries

Abstract: We investigate the morphodynamic equilibrium of tidally dominated alluvial estuaries, extending previous works concerning the purely tidal case and the combined tidal‐fluvial case with a small tidal forcing. We relax the latter assumption and seek the equilibrium bed profile of the estuary, for a given planform configuration with various degrees of funneling, solving numerically the 1‐D governing equation. The results show that with steady fluvial and tidal forcings, an equilibrium bed profile of estuaries exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 34 publications
11
97
1
1
Order By: Relevance
“…A formal equilibrium for tidal channel morphology has only been found adopting rigorous simplifications, from one-dimensional analytical or numerical models 59,60 . These idealized models are of conceptual relevance and provide a basic understanding about how tides increase the tide-average sediment transport capacity in case of uniform sediment.…”
Section: Dynamic Morphological Equilibriummentioning
confidence: 99%
“…A formal equilibrium for tidal channel morphology has only been found adopting rigorous simplifications, from one-dimensional analytical or numerical models 59,60 . These idealized models are of conceptual relevance and provide a basic understanding about how tides increase the tide-average sediment transport capacity in case of uniform sediment.…”
Section: Dynamic Morphological Equilibriummentioning
confidence: 99%
“…[], and Bolla Pittaluga et al . [] had modeled long‐term bed profile (reflecting along‐channel variations of cross‐sectionally averaged depth) development in 1‐D estuaries forced by river and tides. River‐tide current interaction is found to be an important mechanism driving TRST and flushing sediment seaward [ Guo et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works focused on the long-term evolution of tidal channels imposed a fixed boundary condition at the tidal mouth (i.e. (Lanzoni and Seminara, 2002;Todeschini et al, 2008;Yu et al, 2012;Bolla Pittaluga et al, 2015). During the flood phase they prescribed a sediment load in equilibrium with the local hydrodynamics at this boundary, whereas during the ebb phase the sediment load computed at the inlet is simply assumed to leave the estuary.…”
Section: Discussionmentioning
confidence: 96%
“…Tidal channel morphodynamics is dictated by asymmetries in surface elevations and tidal currents that lead to a net sediment flux directed landward within a tidal cycle (De Swart and Zimmerman, 2009). Laboratory experiments (Tambroni et al, 2005), analytical methods Swart, 1996, 2000;Prandle, 2003;Seminara et al, 2010) and numerical techniques (Lanzoni and Seminara, 2002;Hibma et al, 2003;Yu et al, 2012;Bolla Pittaluga et al, 2015) found that, starting from an arbitrary initial bottom profile, the system asymptotically tends to a long-term morphodynamics equilibrium state with a nearly constant value of the maximum flood/ebb speed. This dynamic equilibrium state is characterized by a vanishing net (tidally-averaged) transport in the entire embayment that results in a shoaling bed with water depths decreasing from the inlet to an emerging shore landward.…”
Section: Introductionmentioning
confidence: 99%